2020
DOI: 10.3390/cells9020260
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor Activation Modulates the Integrity of the Perisynaptic Extracellular Matrix at Excitatory Synapses

Abstract: In the brain, Hebbian-type and homeostatic forms of plasticity are affected by neuromodulators like dopamine (DA). Modifications of the perisynaptic extracellular matrix (ECM), which control the functions and mobility of synaptic receptors as well as the diffusion of transmitters and neuromodulators in the extracellular space, are crucial for the manifestation of plasticity. Mechanistic links between synaptic activation and ECM modifications are largely unknown. Here, we report that neuromodulation via D1-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 94 publications
(125 reference statements)
1
25
0
Order By: Relevance
“…Low level of ACAN mRNA in undifferentiated cultures was previously shown in ADSCs, and in human MSCs from either umbilical cord blood (UCB-MSCs) or bone-marrow (BM-MSCs) ( Mwale et al, 2006a , b ; Guasti et al, 2012 ; Gomez-Leduc et al, 2016 ). This is not surprising, as ACAN is detected in several tissues, including in the brain parenchyma, and not restricted to mature cartilage ( Hering et al, 2020 ; Hermann et al, 2020 ; Mitlohner et al, 2020 ). Also, RUNX2 expression was previously shown in undifferentiated hBM-MSCs ( Mwale et al, 2006a ).…”
Section: Discussionmentioning
confidence: 90%
“…Low level of ACAN mRNA in undifferentiated cultures was previously shown in ADSCs, and in human MSCs from either umbilical cord blood (UCB-MSCs) or bone-marrow (BM-MSCs) ( Mwale et al, 2006a , b ; Guasti et al, 2012 ; Gomez-Leduc et al, 2016 ). This is not surprising, as ACAN is detected in several tissues, including in the brain parenchyma, and not restricted to mature cartilage ( Hering et al, 2020 ; Hermann et al, 2020 ; Mitlohner et al, 2020 ). Also, RUNX2 expression was previously shown in undifferentiated hBM-MSCs ( Mwale et al, 2006a ).…”
Section: Discussionmentioning
confidence: 90%
“…During learning processes in the developing and adult brain, variability of ECM densities and dynamic remodeling has been shown to support learning-dependent plasticity 14,15 . In accordance, systemic injection of dopamine receptor D1 agonists in vivo promote rapid cleavage of the ECM protein brevican 16 . ECM weakening increases lateral diffusion of glutamate receptors at the synapse [17][18][19][20] and alters the balance between inhibition and excitation 21 .…”
mentioning
confidence: 78%
“…Recently, we showed in wildtype mice that brevican was downregulated 48h after auditory training in the auditory cortex (Niekisch et al, 2019). Recently, we further showed that such intrinsic reduction of the ECM integrity in the adult cortex can be linked to the stimulation of D1 dopamine receptors suggesting an activity-dependent and learning-related cellular mechanism (Mitlöhner et al, 2020). Altogether, those studies enunciate the major impact of the integrity of the cortical ECM onto the delicate balance of plasticity and tenacity in the learning brain.…”
Section: Discussionmentioning
confidence: 99%
“…During learning processes in the developing and adult brain, variability of ECM densities and dynamic remodeling has been shown to support learning-dependent plasticity (Cornez et al, 2020; Niekisch et al, 2019). In accordance, systemic injection of dopamine receptor D1 agonists in vivo promote rapid cleavage of the ECM protein brevican (Mitlöhner et al, 2020). ECM weakening increases lateral diffusion of glutamate receptors at the synapse (Frischknecht et al, 2009; Heine et al, 2008; Pandya et al, 2018; Schweitzer et al, 2017) and alters the balance between inhibition and excitation (Lensjø et al, 2017).…”
Section: Introductionmentioning
confidence: 94%